Linguistic Landscape in the Tomb of KH Abdul Hamid Pasuruan City: Language Studies in Public Spaces with a Multimodal – Qualitative - Badriyah Wulandari; Tristan Rokhmawan (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
Language has a very important role in tourist destinations, including religious tourism destinations, the Tomb of KH Abdul Hamid, Pasuruan City. As part of the language used in public spaces, the language used in this tourist destination is interesting to study in terms of form, function, meaning, and value. In this regard, this research is an attempt to describe the form, function, meaning, and value contained in the language used in the tourist destination. This research was conducted qualitatively using a landscape linguistic (LL) and multimodal approach. Sources of data are the languages found on signboards in public spaces in religious tourism destinations of the Tomb of KH Abdul Hamid, Pasuruan City. Research data were collected by shooting using a digital camera and smartphone camera and analyzed using a multimodal approach with semantic, semiotic, and language metafunction theories that were used as benchmarks in describing forms, functions, meanings, and cultural values. Based on the data analysis, the findings of this study can be categorized into four groups. First, the forms of language used in the religious tourism destinations of the Tomb of KH Abdul Hamid, Pasuruan City. Second, the function of language in religious tourism destinations, KH Abdul Hamid's Tomb, Pasuruan City. Third, the meaning contained in the languages used in religious tourism destinations, the Tomb of KH Abdul Hamid, Pasuruan City. Fourth, cultural values in the languages used in religious tourism destinations, the Tomb of KH Abdul Hamid, Pasuruan City.